A Zero Crossing Hybrid Bidirectional DC Circuit Breaker for HVDC Transmission Systems - Geon Kim; Jin Sung Lee; Jin Hyo Park; Hyun Duck Choi; Myoung Jin Lee (Energies, 2021)
With the increasing demand for renewable energy power generation systems, high-power DC transmission technology is drawing considerable attention. As a result, stability issues associated with high power DC transmission have been highlighted. One of these problems is the fault current that appears when a fault occurs in the transmission line. If the fault current flows in the transmission line, it has a serious adverse effect on the rectifier stage, inverter stage and transmission line load. This makes the transmission technology less reliable and can lead to secondary problems such as fire. Therefore, fault current must be managed safely. DC circuit breaker technology has been proposed to solve this problem. However, conventional technologies generally do not take into account the effects of fault current on the transmission line, and their efficiency is relatively low. The purpose of this study is to introduce an improved DC circuit breaker that uses a blocking inductor to minimize the effect of fault current on the transmission line. It also uses a ground inductor to efficiently manage the LC resonant current and dissipate residual current. DC circuit breakers minimize adverse effects on external elements and transmission lines because the use of elements placed on each is distinct. All of these processes are precisely verified by conducting simulation under 200 MVA (±100 kV) conditions based on the VSC-based HVDC transmission link. In addition, the mechanism was explained by analyzing the simulation results to increase the reliability of the circuit in this paper.